Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep26761
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-derived osteoblasts and osteoclasts together promote bone regeneration in 3D biomaterials

Abstract: Bone substitutes can be designed to replicate physiological structure and function by creating a microenvironment that supports crosstalk between bone and immune cells found in the native tissue, specifically osteoblasts and osteoclasts. Human induced pluripotent stem cells (hiPSC) represent a powerful tool for bone regeneration because they are a source of patient-specific cells that can differentiate into all specialized cell types residing in bone. We show that osteoblasts and osteoclasts can be differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 41 publications
(61 reference statements)
3
107
0
1
Order By: Relevance
“…Recently, several studies have produced bone-like matrix by seeding human PSCs on different 3D scaffolds [4043] and using perfusion bioreactors [44, 45]. Jeon et al used a biomimetic approach to regenerate bone by 3D coculture of human PSC-derived osteoblasts and osteoclasts within a synthetic scaffolds [46]. We have recently developed protocols to direct the differentiation of hESCs to vascular cells [20, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have produced bone-like matrix by seeding human PSCs on different 3D scaffolds [4043] and using perfusion bioreactors [44, 45]. Jeon et al used a biomimetic approach to regenerate bone by 3D coculture of human PSC-derived osteoblasts and osteoclasts within a synthetic scaffolds [46]. We have recently developed protocols to direct the differentiation of hESCs to vascular cells [20, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Another alternative can be represented by the use of human iPSCs (hiPSCs), which have been recently employed in bone TE for regenerative applications (TheinHan et al, 2013; Kang et al, 2014; Tang et al, 2014; Jeon et al, 2016; Ji et al, 2016). These cells may constitute an interesting cell source for the design of in vitro models of healthy and pathologic bone tissue.…”
Section: Bone In Vitro Modelsmentioning
confidence: 99%
“…An attractive alternative to cell lines is bone cells derived from induced pluripotent stem cells (iPSCs). These would be the ideal resources for the necessary human cell studies and groups have already demonstrated that iPSCs can be used to derive osteoblasts 110 and osteoclasts 111 .…”
Section: Future Directionsmentioning
confidence: 99%